The Impact of Paid Paternity Leave Reforms on Divorce Rates in Europe - Marina Morales (Global Labor Organization (GLO), 2025)
Using a panel dataset covering 27 European countries over a 53-year period, this study examines the relationship between paid paternity leave reforms and divorce rates. Controlling for policyrelated factors and other legislative changes affecting divorce, the dynamic analysis reveals that while the introduction of any paid paternity leave is initially associated with higher divorce rates, the effect becomes negative when focusing on policies offering 2 weeks or more of leave. The decrease in divorce rates becomes more significant as the length of leave increases and grows over time. Specifically, providing fathers with at least 2 weeks of paid leave after childbirth reduces divorce rates by 0.36 percentage points 15 years after implementation. Additional analyses of the underlying mechanisms suggest that, in the absence of extended paternity leave, the results are likely driven by improved labor market opportunities for women-a factor that may unintentionally increase the likelihood of divorce.
Keywords: J48; J12; J16; 330; Paid paternity leave; divorce rates; Europe